LOCUS OF CONTROL AS CORRELATE OF UNDERGRADUATES’ ACADEMIC ACHIEVEMENT IN COLLEGES OF EDUCATION IN IMO STATE (Journal of Guidance and Counselling Studies, 2023)
The aim of this study is to examine locus of control as correlate of undergraduates’ academic achievement in Colleges of Education in Imo State. In specific terms, the study will examine the type of relationship existing between locus of control and academic achievement of undergraduates in General English in colleges of education in Imo state; the type of relationship existing between locus of control and academic achievement of undergraduates in General Mathematics in colleges of education in Imo state. Correlation Survey research design The study adopted the correlation survey design.The sample for this study comprised 195 NCE undergraduates from Alvan Ikoku College of Education, and 65 NCE undergraduates from Imo State College of Education. The sample size for this study will be selected using the multi-stage sampling procedure. The instruments that were adopted for data collection are locus of control scale of Asthon Trice and self-efficacy scale. Also, the undergraduate students’ academic achievement scores in General English Language and General Mathematics for 2021/2022 academic sessions were collected and used.The instruments adopted for data collection in this study were re-validated by different authors to sooth the Nigerian setting. Similarly, the reliability coefficient adopting a test-retest method was 0.75 as reported by other scholars who have adopted the instruments for their studies in the Nigerian setting. The administration of the instrument was done through direct delivery approach. Data collected for this study was analyzed using Pearson Product Moment Correlation Coefficient (r). Similarly, Multiple Regression Analysis was used to analyze research questions 9 and 10, where the R, R2, and adjusted R2 were established for the data collected. The findings further revealed a very low negative relationship between undergraduates’ locus of control and their academic achievement in General English language and General Mathematics in Colleges of Education in Imo state.A significant relationship existing between locus of control and academic achievement of undergraduates in General English language in Colleges of Education in Imo State, while no significant relationship exists between locus of control and academic achievement of undergraduates in General Mathematics in Colleges of Education in Imo State. The conclusion of this study creates an insight on the possible reasons for poor academic achievement among undergraduates in colleges of education in Imo State.
Keywords: Locus of control, academic; achievement; undergraduates; Colleges of education; general English language; general Mathematics